2007
DOI: 10.1111/j.1365-2222.2007.02801.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteopontin expression in a murine model of allergen‐induced airway remodelling

Abstract: OPN expression in the lungs is increased in a murine model of allergen-induced chronic airway remodelling, suggesting a role for this cytokine in airway remodelling in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 49 publications
(68 reference statements)
6
65
2
Order By: Relevance
“…RNA samples were reverse transcribed and subjected to PCR analysis (MiniCycler; MJ Research, Waltham, MA) as we have previously detailed (27). The following primers were used: forward, FLIP L (the long isoform of FLIP) 59TGCTGAAGTCATCCAT CAGG39; reverse, FLIP L 59ATTCCTAGGGGC TTGCTCT39.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…RNA samples were reverse transcribed and subjected to PCR analysis (MiniCycler; MJ Research, Waltham, MA) as we have previously detailed (27). The following primers were used: forward, FLIP L (the long isoform of FLIP) 59TGCTGAAGTCATCCAT CAGG39; reverse, FLIP L 59ATTCCTAGGGGC TTGCTCT39.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…13 The elevated OPN levels found in subepithelial inflammatory cells of asthmatic airways suggests that eosinophils may be a cellular source of this mediator. 14 Venom immunotherapy has been shown to increase OPN levels significantly, 15 and animal studies demonstrate that OPN levels are increased in allergen-induced chronic airway remodelling, whereas OPN J-J Zhao, L Yang, F-Q Zhao et al…”
Section: Introductionmentioning
confidence: 99%
“…12 Studies of endobronchial biopsies from asthma patients have found increased OPN immunostaining in the epithelial layer, as well as in eosinophils, macrophages and lymphocytes present in the submucosal inflammatory infiltrate. 13,14 Xanthou et al 13 found that OPN has a bimodal immunomodulatory effect in a murine model of allergen-induced airway inflammation: a Th2-enhancing effect was observed during antigenic sensitization, and a Th2-repressor effect was seen during antigen challenge. These effects are mediated by the inhibition of migration of plasmacytoid and conventional dendritic cells, respectively.…”
mentioning
confidence: 99%
“…[16][17][18] Further, several human studies have suggested that osteopontin level is increased in airway of asthmatic subjects and is associated with various asthma phenotypes. 15,[20][21][22] Additionally, the chromosomal region of 4q24 where SPP1 gene is located (4q21-q25) has been reported to be associated with atopy and with atopic disease in asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin deficiency, either through administration of blocking antibody or genetic deficiency (knockout mice), has been reported to be protective against airway hyperresponsiveness (AHR) and airway remodeling in these murine models. [15][16][17][18][19] In humans, immunohistochemistry of endobronchial biopsies has shown increased osteopontin expression in bronchial epithelial cells and subepithelial inflammatory cells in asthmatic subjects compared with nonasthmatic controls. 15 In addition, several recent studies have reported an increased level of osteopontin in bronchoalveolar lavage fluid and induced sputum in asthmatic subjects.…”
Section: Introductionmentioning
confidence: 99%